Playing for keeps - Brooke, Lauren (New York : Scholastic, 2006)
Lani must convince her parents not to have her transferred from Chestnut Hill to another school.
RL 4.
Ages 8-13.
960
Accelerated Reader AR
Keywords: Parent and child -- Juvenile fiction; Boarding schools -- Virginia -- Juvenile fiction; Horses -- Training -- Juvenile fiction; Parent and child -- Fiction; Boarding schools -- Fiction; Horses -- Training -- Fiction; Virginia -- Juvenile fiction; Virginia -- Fiction